Religion and life cycles in early modern England (Seventeenth- and eighteenth-century studies ;, 2021)
This innovative, interdisciplinary collection addresses religion and the life course in England c. 1550-1800. Considering Catholic, Protestant and Jewish experiences of biological, social and religious life stages, it suggests new ways of framing the multiple, overlapping life cycles that early modern individuals experienced.